Studi Komparatif Teori Air Thales Dengan Teori Air Dalam Konsep Al-qur’an - Nadhor, M. Fathun (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The initial idea for writing this paper originated from the author's anxiety to find an answer to whether there was a common thread that connected or relatedness and harmony between Ancient Greek philosophy and Islamic teachings, focused on a discussion of the theory of water put forward by Thales, the pioneer of ancient Greek philosophy in the 6th century BC. in line with the theory of water contained in the Qur'an which was revealed to the Prophet Muhammad SAW. in the mid 6-7 AD range. I think we have encountered a lot of research and discussions about ancient Greek philosophy, especially thoughts about Thales, but the author found a gap that has not been discussed, namely whether there is harmony between these two seemingly different points of view, which is philosophy. is guided by rational reason while Islamic teachings are guided by revelation, so in this research the author has found common points of similarities and differences which I will explain below. In this research the author uses a descriptive comparative analysis method and examines various related sources, hopefully it will be useful for readers